Sich haftbar wissen. Wie die russischsprachige Anti-Kriegslyrik seit 2022 Schuld und Verantwortung thematisiert - Obermayr, Brigitte (Wiener Slawistischer Almanach, 2025)
The article discusses anti-war poetry written by Russian poets after the beginning of Russia’s full-scale invasion of Ukraine in February 2022. The analysis focusses on poems that address guilt and responsibility of Russian citizens for this war and the atrocities caused by it. The philosophical discussions on ‘German guilt’ for World War II and the Holocaust (Karl Jaspers, Hannah Arendt) serve as the theoretical framework for the analysis. Here, the article is highlighting Arendt’s notion of collective responsibility, and thus starts with discussing poems that negotiate the overall issue of the responsibility of “us/we” and/or “me/I”, then focusing on poems reflecting the intelligentsiia’s role in this debate. The article discusses poems by Aleksandr Skidan, Mariia Stepanova, German Lukomnikov, Roman Osminkin, Nikolai Karaev and Dariia Serenko.